Launching a Kid Meat Goat Geographical Indication in Albania Territorial Value Chain Issues coming from the Hasi Regional Analysis – Northern Albania - Medolli B.; Bernard C.; Dobi P.; Garnier A.; Lerin F. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
BiodivBalkans project’s ambition is to identify and protect agrobiodiversity as a driver for a sustainable agricultural development in Albanian mountainous regions. In order to address the territorial dimension of local value chains, Geographical Indications (GI) was identified as a possible adequate sign of sustainability and origin to be developed. The Hasi goat (endemic breed) and its kid goat meat were selected by the project in accordance with the Albanian Ministry of Agriculture, with the support of a national Development Agency and implemented by a local NGO. To inform a successful GI building process in Albania and direct support to the value chains with a territory-based action four main points of attention have been identified by the “reflexive pole” of the project: (1) a strong delimitation of the area of origin based on geo-morphological criteria, on the agrarian system history and contemporary evolutions; (2) a detailed goat flock analysis, to better understand the situation of the breed and its outputs in term of production and also to suggest, to the authorities, possible measures of support; (3) the marketing of the breed’s products, with the specific attention to the local bottlenecks in order to secure the market premium already acknowledged among Albanian actors; (4) the environmental issue, grazing practices and their relation to the quality of meat and specification to be potentially included in the book of requirement (of the GI).
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)